Financial Distress pada Perusahaan Initial Public Offering (IPO) - Victoria Ari Palma Akadiati; Imelda Sinaga; Desiderius Novena Kosta (Ekonomis: Journal of Economics and Business, 2022)
Research on companies that conducted initial public offerings in 2018 was conducted with the aim of knowing the effect of cash flow, profit, total debt on financial distress. The sample selection was carried out by purposive sampling technique and is a qualitative research that uses multiple linear regression data analysis techniques using operating cash flow ratios, return on assets ratios, total debt using leverage and the Altman Z "-Score method used in measuring financial distress variables. Hypothesis testing obtained the results of this study is that cash flow and profit have no significant effect on financial distress, while total debt has a significant effect on financial distress of 0.002. The implication of this research is that companies conducting IPOs pay more attention to their ability to pay debts and reduce the amount of debt so that companies can reduce the risk of financial distress.